Light chain deposition disease in kidney: A review of the literature - Pant, AD; Solez, K (Journal of Pathology of Nepal, 2011)
Light chain deposition disease is a rather uncommon monoclonal gammopathy with predominantly renal manifestations with presence of monoclonal light chains in serum and urine. It usually occurs in elderly male patients but can have a wide age range. Patients usually present with proteinuria and some renal dysfunction, but other organs like the liver and heart may also be involved and lead to the death of the patient. The survival of the patients is only about 18 months and benefit of renal transplantation in these patients is debatable, because of high chances of recurrence. Typical light microscopic diagnostic features are important to recognize this disease, which include mesangial nodules and thickening of tubular and glomerular basement membranes. Immunofluorescence shows a monoclonal pattern for kappa light chain, or much less commonly lambda light chain. Electron microscopy is further invaluable in identifying the granular deposits in the mesangial nodules and basement membranes. Keywords: Light chain deposition disease; Renal failure; Plasma cell dyscrasia; Immunofluroescence; Electron microscopy DOI: 10.3126/jpn.v1i1.4454 Journal of Pathology of Nepal (2011) Vol.1, 56-59